Effect of Sulfate on the Aggregation of Clay Particles in Loess - Gu, Liuyang; Zhang, Jingke; Guo, Lianxing; Lv, Qingfeng (Frontiers in Earth Science, 2022)
The type and structure of clay minerals are among the main factors affecting the physical and mechanical properties of loess, and the salt content plays a dominant role in many factors affecting aggregation. In this paper, the grain size analysis, Atterberg limits tests, scanning electron microscope (SEM), energy spectrum analysis (EDS) were used to explore the microstructure and physicochemical mechanisms of the aggregation of clay particles. Finally, the unconfined compressive test, direct shear test and elastic wave velocity test were conducted to explore the effect of sulfate agglomeration on loess properties. The results show that the salt washing process leads to the loss of the original soluble salt, the dispersion of the original aggregates and the increase of fine particles such as fine silt and clay. With the increase of sulfate content, the content of fine silt and clay decreases, the liquid limit and plasticity index decrease, and the plasticity limit remains unchanged, the aggregate content of fine silt and clay increases, the adsorption capacity weakens, and the diffusion layer compresses and thins. The mechanical test results show that, when the sulfate content is less than 3%, the sulfate is almost completely dissolved and the aggregate is less, which can make the compressive strength and the cohesion increase; when the sulfate content is more than 3%, too much sulfate cannot be dissolved and precipitated so that the aggregate increases. However, the existence of large volume mirabilite crystals reduces the cementation, which reduces the compressive strength, increases the internal friction angle, and weakens the cohesion.